KEJAYAAN MUHAMMAD AL-FATIH DALAM MENAKLUKKAN KONSTANTINOPEL TAHUN 1453 MASEHI - Fita Nur Fitriana; Monika Putri; Nandan Devi Nurhayati; Syifa Muhanditsah (Nusantara Hasana Berdikari, 2022)
Muhammad Al-Fatih became the leader of the Ottoman Empire at the age of 22. The failure of his predecessors in the attempt to conquer Constantinople provided a lesson for Muhammad Al-Fatih, so that when he became leader in 1451 AD, he immediately set his sights and was serious about conquering Constantinople, and Constantinople was successfully conquered in 1453 AD. So that our group will conduct a mini research entitled The triumph of Islam under the Muhammad Al-Fatih Empire by using the literature study method on various appropriate sources. The purpose of this mini-research is to find out historical facts about the glory of Islam under the Muhammad Al-Fatih Empire in conquering Constantinople. The seat of the Byzantine government was in Constantinople, which was strategically located for the world. The conquest of Constantinople was inspired by the promise of Islamic teachings to study the things that caused the failure of previous conquests carried out by Islamic leaders or the Ottoman Empires to successfully conquer Constantinople.